Beneficial microbial signals from alternative feed ingredients: a way to improve sustainability of broiler production?. Issue 5 (25th August 2017) - Van Immerseel, Filip; Eeckhaut, Venessa; Moore, Robert J.; Choct, Mingan; Ducatelle, Richard
Summary: More sustainable broiler meat production can be facilitated by the increased use of cheap by‐products and local crops as feed ingredients, while not affecting animal performance and intestinal health, or even improving intestinal health, so that antibiotic usage is further reduced. To achieve this, knowledge of the relationship between the taxonomic and functional microbiota composition and intestinal health is required. In addition, the relationship between the novel feed sources, the substrates present in these feed sources, and the breakdown by enzymes and microbial networks can be crucial, because this can form the basis for development of tailored feed‐type specific solutions for optimal digestion and animal performance.